Policing the Crisis in the 21st Century; the making of "knife crime youths" in Britain - Williams, Elaine (Crime, law and social change, 2024)
The terms ‘knife crime’ and ‘knife culture’ were first established in British crime discourse at the turn of 21st century and represent a particular re-making of youth in post-industrial Britain. The generational impacts of advanced neoliberalism have intensified conflict between marginalised young people in the UK as they compete for success in high-risk informal economies and navigate the normalised brutalities of everyday violence. However, the impact of extreme inequality and structural violence on children has not been central in the response to youth-on-youth knife homicides in the 2000s and 2010s. Instead, these decades have been characterised by punitiveness and surveillance, increasing discriminatory stop and search practices and extending powers that target and control young people. Through conjunctural analysis of the making of ‘knife crime youths’ in the UK, this paper considers how shifting forms of cultural racism have been able to rearticulate child violence as cultural deficit, using race once again to work through the contradictions of late capitalism. Applying a radical criminological understanding of deviance labelling as a specific response to crime, this paper asks: To what extent is the construction of ‘knife crime’ a continuation of Policing the Crisis in the 21st century? And why has this process been relatively uncritiqued by practitioners and academics that contribute to ‘knife crime’ discourse? Using document, archive and discourse analysis this paper presents a social history of ‘knife crime youths’, depicting the formative interactions that have so far been obscured by the matter-of-fact dominance of the label and its practices.